MEANING AND FUNCTION OF ANCIENT MANUSCRIPTS FOR THE CULTURE AND NATIONAL DEVELOPMENT THROUGH TEACHING HISTORY - Saraswati, Ufi (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
The Indonesian people still keep old manuscripts in considerable amounts. The distribution of ancient manuscripts is found in almost all regions of the Indonesian archipelago, although the amount of ancient manuscripts in each region is not the same. The old manuscript can also be expressed as a document of a nation because the document is defined as an article containing crucial information. Today, they were teaching history using an ancient manuscript still rarely carried out by the teachers. However, it needs to attempt to understand the ancient texts that all information about the past delivered to the present and future generations. Teaching history that relies on scarce resources has brought new challenges for teachers. In this country, history science has become one of the compulsory subjects in the curriculum; since elementary school, there is a question, has history teaching has run well? Teaching history in schools is more than transferring teachersâ€™ knowledge to students in the classroom through one-way communication. Pupils just become passive objects that must memorize the teacherâ€™s notes in order to answer the questions that will be tested. This kind of teaching history method has made history a boring lesson. As for to make history teaching successful, the method used should be constructed â€œhistorical memoryâ€ accompanied by â€œemotional memories.â€ The study of ancient texts in teaching history can be regarded as one of the methods that can lead to â€œemotional memories.â€ After students are given the facts of history to construct â€œhistorical memoryâ€ in the classroom, emotional memory can be explored by studying the ancient texts. Several alternative methods with the modification of history teaching need to be developed. One method that researcher through think could be applied is the utilization of the ancient manuscript to the teaching of history, particularly for the development of Culture and National Character